A performance study of a fractal UWB antenna for on‐body WBAN applications. Issue 9 (September 2017) - Tripathi, Shrivishal; Mohan, Akhilesh; Yadav, Sandeep
Abstract: The antenna performance is affected strongly in proximity of human body in wireless body area network (WBAN). In this study, a fractal ultrawideband antenna is presented, which can operate in free space as well as on‐body WBAN scenario, simultaneously. In the design, Koch fractal geometry is used in the monopole as well as in the ground plane of the antenna, which assists to achieve the operational bandwidth up to 122% and stable radiation pattern. In order to analyze the effect of body tissue on antenna performance, a four layered (skin, fat, muscle, and bone) human body tissue model is used. The comparative S 11 performance of the antenna on tissue model for on‐body WBAN scenarios is evaluated. Moreover, S 21 characteristics of antenna for different orientations at various body parts such as abdomen, near forehead, and chest, are measured to acquire the healthcare signals. Local SAR and average SAR performances of the presented antenna are also evaluated on SAR line. Hence, the proposed antenna is a suitable candidate for WBAN applications.